Social capital: how is it formed? an examination of strategies and processes of social capacity building in selected FIP sites - Tanchuling, Ma. Linnea V. (Quezon City College of Social Work and Community Development, University of the Philippines, Diliman, 2024)
Social capital is a concept that has been discoursed and debated throughout the years. However, the question that many ask is: how is social capital formed? This study attempts to answer this question by pointing out the critical components needed for social capital formation to occur from a community development perspectives.
Social capital is defined in this study as a type of social relations characterized by (i) network ties, roles and roles, (ii) shared understandings, narratives, values, attitudes, and beliefs, and (iii) trust, norms, obligations and identity that is associated with positive community development outcomes, ie. participation in civil society organization that deliver public goods and services to the community. It applies to both the individual and the collective. However, since social capital resides in social relationships, it requires the inclination and availability of other to be realized (Claridge, 2018d).
Social capital formation is correlated to participation in organizations and associative life or civic engagement usually linked to civic attitudes, trust and social networks. Participation in organizations in affected by individual factors such as sex and gender identity, age, race, ethnicity, geography, education, etc. These factors either facilitate or limit entry to organizations. In the case that it limits entry, there is a need to capacitate individuals to form and develop their social capital to engage in social interactions that would improve their personal community life. Corollary to forming, developing and strengthening of individual's social capital in increasing the social capital of organizations and networks.
Social capacity building approach is considered as means to achieve social capital formation and strengthening. Forming and strengthening social capital require understanding how settings (e.g.) social networks, sense of community) can foster support for individuals. Strategies for forming and increasing social capital rests on creating new social networks, linking individuals to existing networks and enhancing existing networks as well as building individual's capacity to link with networks.
The critical components needed for social capital formation that emanated from the community development perspectives are outlined below. These components also serve to guide social development in its pursuit for inclusive, participatory, gender responsive, empowering and sustainable development.
(i) Community organizing acted as catalyst that enabled other social capital formation and strengthening methods (organizational formation and development, leadership development and inter-organizational collaboration) to be inter-connected and inextricably linked;
(ii) Social capital formation and strengthening focused on three (3) major interrelated strategies of organizational formation and development, leadership development and fostering inter-organizational collaboration. The processed and methods of social capacity building necessitated synchronized attention to strengthening individuals, formal organizations and relational networks;
(iii) Social investigation and social analysis as pre-conditions for appropriate strategies and methods for social capital formation to occur. It starts with understanding the context of the communities; and
(iv) Awareness raising and consciousness raising as critical components for social capital formation.
Keywords: Field work (Educational method)